2001
DOI: 10.1159/000050441
|View full text |Cite
|
Sign up to set email alerts
|

Early Treatment of Posthemorrhagic Hydrocephalus in Low-Birth-Weight Infants with Valveless Ventriculoperitoneal Shunts

Abstract: The surgical treatment of posthemorrhagic hydrocephalus (PHH) in low-birth-weight infants (LBWI) is debated. In a few cases, hydrocephalus progresses rapidly and requires early drainage, but valves and ventriculostomy have a high rate of complications in the early phase. Temporary valveless shunt (VLS) is proposed as an alternative treatment of acute PHH in LBWI. Thirteen infants with PHH, weighing less than 2,000 g at birth, were treated with VLS, which was systematically converted into a valve-regulated shun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 25 publications
2
6
1
Order By: Relevance
“…In the present study, infection rate was 8%, which was consistent with the literature data on VSGS. Moreover, our result was found to be considerably lower than the infection rates of other treatment methods reported in the literature [2024]. …”
Section: Why Vsgs (Ventriculosubgaleal Shunt) ?contrasting
confidence: 79%
See 1 more Smart Citation
“…In the present study, infection rate was 8%, which was consistent with the literature data on VSGS. Moreover, our result was found to be considerably lower than the infection rates of other treatment methods reported in the literature [2024]. …”
Section: Why Vsgs (Ventriculosubgaleal Shunt) ?contrasting
confidence: 79%
“…Rahman et al [19] reported no infection development after carrying out VSGS and VPS procedures on 15 premature infants with PHH and a birth weight below 1,500 g. Moreover, in the absence of VSGS treatment, the infection rate after early VPS treatment in premature infants with PHH was found to be increasing from 20 to 50% by Vinchon et al [20] and as 45.2% by Reinprecht et al [2]. Infection rates of other methods used in PHH treatment in large series in the literature are reported to be 15.9–16.4 [21] in subcutaneous reservoir method and 10–27% in EVD method [22].…”
Section: Why Vsgs (Ventriculosubgaleal Shunt) ?mentioning
confidence: 99%
“…20,21 EVD is, however, associated with a high risk of infection especially in preterm infants with an incompetent immune system. 5,10,12,22,23 Infants with meningitis are at a particularly high risk for later shunt dependence and disability. 10 As a result of the high risk of infection, EVD is not recommended routinely.…”
Section: Discussionmentioning
confidence: 99%
“…The indications for vp shunt surgery vary and are controversially discussed. 22 Important factors are indisputably head growth 2,10,11 and an increase in ventricular width 18,25 when punctures are discontinued or performed less frequently. It is interesting to note that CSF protein content rarely plays a role in a decision for or against definitive shunt placement although the efficacy of CSF reabsorption decisively depends on CSF protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the most common definitive treatment for these patients is VP shunting. Slit ventricles and multiple episodes of shunt failure are problematic in many infants and preterm neonates shunted for hydrocephalus [2,6]. Prematurity favors shunt infections due to presumed immature immune systems [7].…”
Section: Discussionmentioning
confidence: 99%